A Benders decomposition based framework for solving cable trench problems. (May 2017) - Calik, Hatice; Leitner, Markus; Luipersbeck, Martin
Highlights: Algorithmic framework based on Benders decomposition applicable to different variants of the cable trench problem (CTP). Benders decomposition approach including stabilization and primal heuristics. Computational study addressing three variants of the CTP. Abstract: In this work, we present an algorithmic framework based on Benders decomposition for the Capacitated p -Cable Trench Problem with Covering. We show that our approach can be applied to most variants of the Cable Trench Problem (CTP) that have been considered in the literature. The proposed algorithm is augmented with a stabilization procedure to accelerate the convergence of the cut loop and with a primal heuristic to derive high-quality primal solutions. Three different variants of the CTP are considered in a computational study which compares the Benders approach with two compact integer linear programming formulations that are solved with CPLEX. The obtained results show that the proposed algorithm significantly outperforms the two compact models and that it can be used to tackle significantly larger instances than previously considered algorithms based on Lagrangean relaxation.